Subdural hematomas in pulmonary arterial hypertension patients treated with prostacyclin analogs - Louis, Lam (Medknow Publications & Media Pvt Ltd, 2012)
Prostacyclin analogs therapy has been associated with development of thrombocytopenia. Little is known whether this treatment increases the risk of intracranial hemorrhage in pulmonary artery hypertension (PAH) patients. We queried the Cleveland Clinic billing database to identify cases of nontraumatic sudural hematoma (SDH) in patients with PAH. We identified those individuals who were receiving prostacyclin analogs therapy at the time of the neurological event and assessed whether these patients were also taking antiplatelet or anticoagulation therapies. We identified three cases of nontraumatic SDH in 856-patient-year of prostacylin analog treatment. All patients were women, had low normal platelet counts or thrombocytopenia, and were concomitantly receiving anticoagulation therapy in the appropriate therapeutic anticoagulation range. All three patients were managed conservatively and had no neurologic sequelae. Nontraumatic acute subdural hematoma is a rare event in patients with PAH treated with prostacyclin analogs. All affected patients were concomitantly receiving anticoagulation therapy.